Serum Clusterin: A Potential Marker for Assessing the Clinical Severity and Short-Term Prognosis of Hepatitis B Virus-Related Acute-on-Chronic Liver Failure - Liu, Huimin; Li, Yuxin; Gao, Fangyuan; Meng, Peipei; Yu, Hao; Wu, Tong; Zhou, Yang; Jiang, Yuyong; Wang, Xianbo (Disease Markers, 2020)
Background. Acute-on-chronic liver failure (ACLF) is a clinical syndrome characterized by acute deterioration of liver function and high short-term mortality. Clusterin, with biological functions similar to small heat shock proteins, can protect cells from apoptosis induced by various stressors. The aim of this study was to detect the level of serum clusterin in hepatitis B virus- (HBV-) related ACLF and to assess the predictive value of clusterin for the short-term prognosis of HBV-ACLF. Methods. We detected serum clusterin by ELISA in 108 HBV-ACLF patients, 63 HBV-non-ACLF patients, and 44 normal controls. Results. Serum clusterin was markedly lower in HBV-ACLF patients (median, 51.09 μg/mL) than in HBV-non-ACLF patients (median, 188.56 μg/mL) and normal controls (median, 213.45 μg/mL; all P<0.05). Nonsurviving HBV-ACLF patients who died within 90 days had much lower clusterin levels than did surviving patients, especially those who died within 28 days (nonsurvival group vs. survival group: 39.82±19.34 vs. 72.26±43.52, P<0.001; survival time≤28 vs. survival time>28: median 28.39 vs. 43.22, P=0.013). The results showed that for identifying HBV-ACLF, the sensitivity of clusterin (93.7%) was similar to the sensitivities of the international normalized ratio (INR; 94.4%) and total bilirubin (TBIL; 94.8%), but its specificity (90.7%) was higher than that of prothrombin activity (PTA; 65.8%) and TBIL (69.8%) and was similar to INR (88.9%). As the concentration of clusterin increased, the mortality of HBV-ACLF patients decreased significantly from 59.3% to 7.0%. Clusterin had better ability for predicting the prognosis of HBV-ACLF patients than did the model for end-stage liver disease (MELD) score and the chronic liver failure consortium (CLIF-C) ACLF score (MELD vs. clusterin: P=0.012; CLIF-C ACLF vs. clusterin: P=0.031). Conclusion. Serum clusterin is a potential biomarker for HBV-ACLF which can be used to assess clinical severity and the short-term prognosis of patients with this disease and may help clinicians identify HBV-ACLF with greater specificity and improved prognostic accuracy than existing prognostic markers.